Urban drivers of plant‐pollinator interactions. (19th June 2015) - Harrison, Tina; Winfree, Rachael
Summary: Plant–pollinator interactions are affected by global change, with largely negative impacts on pollination and plant reproduction. Urban areas provide a unique and productive study system for understanding the impacts of many global change drivers on plant–pollinator interactions. We review the mechanistic pathways through which urban drivers alter plant–pollinator interactions. The literature on urban drivers of plant–pollinator interactions is small but growing and has already produced exciting insights about how population processes or pollinator behaviour interacts with landscape urban drivers to affect pollination outcomes. Habitat loss and fragmentation can change flower visitation rates and pollination success through changes in pollinator foraging behaviour or through population‐level effects on pollinators. Urban environments, where impermeable surface provides an inhospitable matrix, may allow researchers to identify habitat fragments more clearly than in many other environments. Recent studies have found that non‐native plants are not differently preferred by pollinators relative to native plants, therefore removing the basis for expecting pollinator‐mediated competition between native and non‐native plants in urban habitats. However, non‐native species together with managed vegetation may have powerful effects in urban habitats via changes in community‐level plant phenology and consequent changes in pollinator phenology. The current level of climate warming has not caused plants and pollinators to become detectably temporally separated, although at the same time, diversity among species' phenological responses could buffer plant–pollinator interactions from climate variation. Due to the urban warming effect, cities provide a promising system for better understanding the warming effects on plant–pollinator interactions. Environmental contaminants such as soil nitrogen and heavy metal pollution have been examined with respect to plant–pollinator interactions in small‐scale, mechanistic studies. The extent to which environmental contaminants drive plant–pollinator interactions in actual urban landscapes is, however, currently unknown. Important knowledge gaps that require research attention include understanding the consequences of plant and pollinator trait filtering on plant–pollinator interactions, and expanding the literature to include underrepresented biomes and pollinator taxa. Abstract : Lay Summary